Scientific substantiation of engineering preparation measures due to the influence of construction in the dense building conditions - Stefanyshyna-Gavryliuk, Yulija D. (КНУБА, 2020)
The method of studying the stress-strain state of reinforcement structures of combined soil massifs has been proposed with the geometric and physical nonlinearity in the formulation of the problem based on the nonlinear theory of elasticity and plasticity of the soil. The study of the stressdeformed state of the computational domain from the standpoint of the mechanics of the deformed solid body had been carried out, using algorithms for solving the problems of the theory of elasticity and plasticity, with the construction of universal computational models of the combined half-space, that allows to determine more reasonably the magnitude of the stress-strain state of complex soil bases in interaction with the reinforcement structures, the surrounding buildings foundations and the whole complex of the surrounding buildings structures. The influence of new construction on the condition of soil bases and foundations of adjacent buildings had been evaluated by determining the change of pressure on the reinforcement structure and determining the stress-strain state change of this structure and the foundation of the existing house. The change in the deformation of the foundation of the existing building, ie the oscillation of the soil foundation and the maximum amplitude of uneven subsidence of the foundations of the existing building have been determined. Each formulation of the problem had to include its own reliability analysis and a specific approach that requires numerical modeling and development of appropriate measures to scientifically substantiate engineering preparation measures in dense building. Further design of protective reinforcement structures for new construction under the conditions of the building reconstruction has carried out considering the impact on the existing buildings and structures and the adjacent soil mass of different stages of construction, begining with the arrangement of protective reinforcement structures, the development of a excavation due to the effect of unloading the foundation, and the sequence of erection of engineering structures.
Наукове обґрунтування заходів з інженерної підготовки з урахуванням впливу будівництва в умовах щільної забудови
Keywords: new construction; scientific substantiation; stress-strain state; reinforcement structures; engineering preparation; нове будівництво; наукове обґрунтування; напружено-деформований стан; конструкції укріплення; інженерна підготовка; 711.1